2021
DOI: 10.1590/1676-0611-bn-2019-0821
|View full text |Cite|
|
Sign up to set email alerts
|

Type of shelter and first description of the echolocation call of disk-winged bat (Thyroptera devivoi)

Abstract: Thyropteridae is a family of bats endemic to the Neotropical region, and Thyroptera devivoi is the only species in the family that occurs exclusively in forest patches within savannas of northern South America and north of the Brazilian Cerrado. Primary data on the species are still scarce. Therefore, in this study our objective was to fill knowledge gaps on geographical distribution, roost-use, and echolocation for the species. We observed a T. devivoi colony of 15 individuals living under a dead palm leaf. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Thus, within Colombia, T. lavali is known to occur only in the Amazon region. Recently, Rosa et al (2020) described the echolocation calls and shelters of T. devivoi. However, we think that the bat showed by Rosa et al (2020: fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, within Colombia, T. lavali is known to occur only in the Amazon region. Recently, Rosa et al (2020) described the echolocation calls and shelters of T. devivoi. However, we think that the bat showed by Rosa et al (2020: fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroptera devivoi is known from six localities: one in the Colombian llanos, one in the Guyanan Rupununi savanna, and four in the Brazilian Cerrado (Maranhão, Tocantins, and Piauí states) (Gregorin et al, 2006;Santos, C. et al, 2013;Rodríguez-Posada et al, 2017;Rosa et al, 2020). There is scarce information on the ecology of this recently-described species: one individual from Guyana was captured 'under and eaté palm leaf' (Gregorin et al, 2006); in Colombia, a specimen was caught in a Mauritia flexuosa L. f. grove (Rodríguez-Posada et al, 2017); and in Maranhão state, Brazil, a roosting group was found in a dead palm leaf sheath (Rosa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%